Fire, rituals and domesticity. Forest resource management in the sub-Andean region of Jujuy, Argentina (2000 BP): First anthracological evidence - Ortiz, María Gabriela (2017)
Anthracological analysis results from an archaeological site located on the foothill of the Argentinian northwest, assigned to the lower Formative period (2,000 year BP) is presented. Thirty four charcoals of different depositional events on an excavated area of 94 m2 were analyzed. Most of them were assigned to Mimosoideae-Fabaceae. It is appreciated that the most representative taxonomic group generally corresponds to species with excellent fuel properties. Others species, represented at the carpological level and belonging to plants with value food and dye, have not been identified at an anthracological level. Some woody species were selected for specific functions, like human body cremations as complex funerary rituals; while others were elected to obtain a high heat power on pyretic structures (earth oven). The diversity of identified taxa in the different sampled events indicates both the provisioning of available species and the knowledge of properties for different types of usage e.g. Fabacea and Anacardiaceae. The presence of Salix in earth oven and Allophylus in clustered in small groups of charcoals on the floors evidence an environment with humid seasons, and a population that lived near a body of water possibly permanent.